Computerised Information System for Libraries - Appa Rao, Allam; Sugunamma, Gogula (Journal of Information and Knowledge, 1987)
Presents a system analytic approach, to development of a computer-based library and Information system. The role of vocabulary control devices, profile design and query-database structural matching are presented as a basic input for selective information service development.